Self Management in Improving the Quality of Lecturers - Sri Nurabdiah Pratiwi; Sri Ngayomi Yudha Wastuti; Jamila Jamila (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
Improving the quality of educators, especially lecturers, must be carried out continuously and continuously. For this reason, it is necessary to reorganize or manage oneself on an ongoing basis to achieve these qualities. This form of self-management is known as self-management. Implementing self management needs to understand the concept of management first, which is known as POAC. The application of management is not only carried out by an organization, but humans as individuals who have the potential to apply management within themselves. In relation to this self-management, humans will be more professional in their activities, because they understand their own condition and surrounding conditions. The application of self-management through POAC will make humans have the ability to plan, organize, implement as well as supervise what are the main priorities in improving their quality, so that success is achieved according to their professional level.